Application of FMICW technology based on stagger algorithm in automotive radar - Yuanhui ZHANG; Jian YANG; Junjiang ZHU; Xiaolu LI; Yuchen HE (Dianxin kexue)
The problem of spurious spectral peaks produced by the traditional method of using a single switching frequency in automotive FMICW radar was focused by the proposed scheme.The system accuracy depended on the previously estimated range if a bandpass filter was utilized to eliminate the spurious spectral peaks,and the noise floor could be too high to achieve the required dynamic detection range if the random interrupted sequence method was utilized.A stagger algorithm based on multiple switching frequencies was used,in which the spurious peaks from the frequency domain could be removed by minimizing each frequency position on multiple spectrums.Simulation results show that the proposed method is close to the equivalent FMCW radar detection performance,and is good in multiple targets scenario.